Desiccant Dehumidification With Hydronic Radiant Cooling System For Air-Conditioning Applicants In Humid Tropical Climates. - Ameen, Ahmadul; Mahmud, Khizir (2005)
This paper discusses the feasibility of a hybird desiccant dehumidification system combined with chilled ceiling for airconditioning applicants in humid tropical climates.